Enhancing multi-objective evolutionary algorithms with machine learning for scheduling problems: recent advances and survey - Zhang, Wenqiang; Xiao, Guanwei; Gen, Mitsuo; Geng, Huili; Wang, Xiaomeng; Deng, Miaolei; Zhang, Guohui (Frontiers in Industrial Engineering, 2024)
Multi-objective scheduling problems in workshops are commonly encountered challenges in the increasingly competitive market economy. These scheduling problems require a trade-off among multiple objectives such as time, energy consumption, and product quality. The importance of each optimization objective typically varies in different time periods or contexts, necessitating decision-makers to devise optimal scheduling plans accordingly. In actual production, decisionmakers confront intricate multi-objective scheduling problems that demand balancing clients' requirements and corporate interests while concurrently striving to reduce production cycles and costs. In solving various problems, multi-objective evolutionary algorithms have attracted the attention of researchers and gradually become one of the mainstream methods to solve these problems. In recent years, research combining multi-objective evolutionary algorithms with machine learning technology has shown great potential, opening up new prospects for improving the performance of multi-objective evolutionary methods. This article comprehensively reviews the latest application progress of machine learning in multi-objective evolutionary algorithms for scheduling problems. We review various machine learning techniques employed for enhancing multi-objective evolutionary algorithms, particularly focusing on different types of reinforcement learning methods. Different categories of scheduling problems addressed using these methods were also discussed, including flow-shop scheduling issues, job-shop scheduling challenges, and more. Finally,we highlighted the challenges faced by the field and outlined future research directions.